Global justice and international labour rights - Daha, Yossi; Lerner, Hanna & Milman-Sivan, Faina / Ed (Cambridge University Press, 2016)
"Despite the growing global consensus regarding the need to ensure minimal labour standards such as adequate safety and health conditions, freedom of association, and the prohibition of child labour, millions of workers across the world continue to work in horrific conditions. Who should be held responsible, both morally and legally, for protecting workers' rights? What moral and legal obligations should individuals and institutions bear toward foreign workers in their countries? Is there any democratic way to generate, regulate, and enforce labour standards in a global labour market? This book address these questions by taking a fresh look at the normative assumptions underlying existing and proposed international labour regulations. By focusing on international labour as a particular sphere of justice, it seeks to advance both the contemporary philosophical debate on global justice and the legal scholarship on international labour"--